Gender differences in long‐term survival post‐transplant: A single‐institution analysis in the lung allocation score era. Issue 3 (8th February 2017) - Loor, Gabriel; Brown, Roland; Kelly, Rosemary F.; Rudser, Kyle D.; Shumway, Sara J.; Cich, Irena; Holley, Christopher T.; Quinlan, Colleen; Hertz, Marshall I.
Abstract: The purpose of this study was to clarify the significance of recipient gender status on lung transplant outcomes in a large single‐institution experience spanning three decades, we analyzed data from all lung transplants performed in our institution since 1986. Kaplan‐Meier curves and Cox proportional hazard models were used to evaluate the effect of recipient characteristics on survival and BOS score ≥1‐free survival. Logistic regression analysis was used to explore the association of gender with short‐term graft function. About 876 lung transplants were performed between 1986 and 2016. Kaplan‐Meier survival estimates at 5 years post‐transplant for females vs males in the LAS era were 71% vs 58%. In the LAS era, females showed greater unadjusted BOS≥1‐free survival than males (35% vs 25%, P =.02) over 5 years. Female gender was the only factor in the LAS era significantly associated with improved adjusted 5‐year survival [HR 0.56 (95% CI 0.33, 0.95) P =.03]. Conversely, in the pre‐LAS era female gender was not associated with improved survival. Female recipients showed significantly improved survival over 5 years compared to males in the LAS era. A prospective analysis of biologic and immunologic differences is warranted.